Blockchain and edge computing technology enabling organic agricultural supply chain: A framework solution to trust crisis - Hu, Sensen; Huang, Shan; Huang, Jing; Su, Jiafu (Computers & industrial engineering, 2021)
•We construct a technique model to resolve the trust issue of organic agriculture by combining the blockchain and edge computing.•Leverage the immutability of blockchain’s DLT and the paradigm of edge computing to reduce the blockchain expenditure.•Propose an improved consensus mechanism and refine four critical roles from all the stakeholders. The credibility of information on organic agri-products has always blocked the participation of small and medium-sized farms in high value-added agriculture. However, the inherent characteristics of the organic agricultural supply chain (OASC)–such as centralization, monopoly, and asymmetry–have repeatedly plunged OASC into the predicament of information non-transparency. Ultimately, it results in a severe trust crisis of consumers. Fortunately, the emerging blockchain and edge computing technology probably raise an opportunity to improve this issue. Despite the overwhelming advantage (such as tamper-resistant, trust-free, transparent, decentralized, and immutable), this technology has to overcome the imperfection of cost and efficiency before it can be employed by OASC, particularly for geographically dispersed small and medium-sized farms in remote areas. In this paper, we first leverage the immutability of blockchain and the paradigm of edge computing to construct an OASC’s trust framework, which has a much better trade-off between cost and efficiency. Further, according to the scenarios of OASC, we divide all the stakeholders into four roles, proposing a novel consensus mechanism to manage the information flow. The evaluation results demonstrate that our proposal can significantly achieve the performance improvement as well as the cost decline compared to the traditional approach. This framework will also make affordable traceability solutions for those in developing countries at a low cost in the future.